NORMA TIVITY OF SCIENTIFIC LA WS (II): ASPECTS OF IMPLICIT NORMA TIVITY. - Mets, Ave (Problems / Problemos, 2018)
In Normativity of Scientific Laws (I) (Mets 2018) explicit and implicit normativities were discerned and it was shown, following Joseph Rouse, that scientific laws implicitly harbour what Alchourrón and Bulygin imply to be the core of normativity. Here I develop this claim by discerning six aspects of implicit normativity in scientific laws: (1a) general and (1b) special conceptual normativity, concerning analytical thinking and special scientific terminologies; (2a) theoretical and (2b) material epistemic normativity, concerning mathematical and experimental accountability of the world; (3a) narrow and (3b) broad practical normativity, concerning technologies in both narrower and broader senses.